ANALISIS FAKTOR-FAKTOR YANG BERKORELASI DENGAN SIKAP KEWIRAUSAHAAN PETERNAK KELINCI (KASUS: KOPERASI PETERNAK KELINCI KABUPATEN BOGOR, JAWA BARAT) - Busrol Karim; Wahyu Budi Priatna (Forum Agribisnis, 2012)
Rabbit agribusiness has high potensi to be developed. This development has to be supported by entrepreneurial behavior of rabbit farmers. The purposes of the research are: 1) to analyze the entrepreneurial level of rabbit farmers, 2) to analyze the correlating factors of entrepreneurial behavior. Respondent selection was conducted by census to all rabbit farmers which were member of KOPNAKCI. Total respondent used was 50 repondents. The method to analyze the entrepreneurial level is summated rating of nine indicators of entrepreneurial attitude. The correlating factors are motivation, education, farming experience, access to inputs, training/counseling and access to information. The correlation is measured by Spearman Rank. The result shows 1) the entrepreneurial level of rabbit farmers is medium, 2) correlating factors for entrepreneurial attitude are training/counseling and access to information.